Molecular Biological Comparison of Dental Pulp-and Apical Papilla-Derived Stem Cells - Smeda, Martyna; Galler, Kerstin Martina; Woelflick, Melanie; Rosendahl, Andreas; Moehle, Christoph; Lenhardt, Beate; Buchalla, Wolfgang; Widbiller, Matthias (International Journal of Molecular Sciences, 2022)
Both the dental pulp and the apical papilla represent a promising source of mesenchymal stem cells for regenerative endodontic protocols. The aim of this study was to outline molecular biological conformities and differences between dental pulp stem cells (DPSC) and stem cells from the apical papilla (SCAP). Thus, cells were isolated from the pulp and the apical papilla of an extracted molar and analyzed for mesenchymal stem cell markers as well as multi-lineage differentiation. During induced osteogenic differentiation, viability, proliferation, and wound healing assays were performed, and secreted signaling molecules were quantified by enzyme-linked immunosorbent assays (ELISA). Transcriptome-wide gene expression was profiled by microarrays and validated by quantitative reverse transcription PCR (qRT-PCR). Gene regulation was evaluated in the context of culture parameters and functionality. Both cell types expressed mesenchymal stem cell markers and were able to enter various lineages. DPSC and SCAP showed no significant differences in cell viability, proliferation, or migration; however, variations were observed in the profile of secreted molecules. Transcriptome analysis revealed the most significant gene regulation during the differentiation period, and 13 biomarkers were identified whose regulation was essential for both cell types. DPSC and SCAP share many features and their differentiation follows similar patterns. From a molecular biological perspective, both seem to be equally suitable for dental pulp tissue engineering.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Dental pulp stem cells; Mesenchymal stem cells; Regenerative endodontics; Stem cells of the apical papilla; Transcriptome